Interpreting God and the postmodern self on meaning, manipulation and promise - Thiselton, Anthony C. (Grand Rapids, MI Eerdmans, 1995)
Includes bibliographical references and indexes.
Keywords: God -- history of doctrines -- 20th century; Self; Hermeneutics -- religious aspects -- Christianity -- history of doctrines -- 20th century; Postmodernism -- religious aspects -- Christianity